A CROSS-SECTIONAL STUDY OF PSYCHOSIS AND PERSONALITY PROFILE IN PATIENTS DIAGNOSED WITH ALCOHOL USE DISORDER - MADAVI, PRIYA; SOMANI, ABHISHEK; VERMA, PRAVIN; SAOJI, ANAND (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The objectives of the study are (1) to study personality profile in patients diagnosed with alcohol use disorder (AUD) and (2) to study incidence of psychosis in patients with AUD. Methods: This was a cross-sectional study conducted in the department of psychiatry of a tertiary care medical college. 70 patients presenting with a history of alcohol intake underwent diagnosis according to the Diagnostic and Statistical Manual of Mental Disorders, 5th edition (DSM-5) criteria for AUD were enrolled in the study on the basis of pre-defined inclusion and exclusion criteria. Post a 2-week detoxification period, psychiatric symptoms encompassing depression, anxiety, hallucinations, and unusual behavior were assessed using the brief psychiatric rating scale (BPRS), while personality profiles were evaluated with the NEO Personality Inventory-3. Alcohol dependence levels were measured using the Severity of Alcohol Dependence Questionnaire. Results: There were 60 (85.71%) males and 10 (14.29%) females. There was a significant male preponderance in studied cases with M:F ratio of 1:0.16. Highest number of patients, i.e., 63 (90%) patients were married, followed by 4 (5.71%) patients were unmarried and 3 (4.29%) patients were divorced. Among 70 studied cases, 5 (7.14%) patients were found to have some or the other degree of psychotic symptoms. There was a significant correlation between being unskilled worker and having low literacy or low income and AUD (p<0.05). There was no statistically significant association between severity of AUD and education (p=0.70), occupation (p=0.94), income (p=0.84), and family history of alcohol consumption (p=0.58). Participants have mild severity shown low to average score on neuroticism, average scores on extraversion, very low to low scores on openness, high to very high scores on agreeableness, and high to very high scores on conscientiousness. Conclusion: We found a significant correlation of AUD with increasing age, male gender, early alcohol initiation, and prolonged dependence. Lower education and unskilled occupations were also linked to AUD. Personality trait analysis revealed distinct patterns based on the severity of physical dependency.